The interplay between entrepreneurship education and regional knowledge potential in forming entrepreneurial intentions - Sascha G. Walter; Dirk Dohse (Kiel Institute for the World Economy (IfW), 2009)
This study examines how the effect of entrepreneurship education on students' entrepreneurial intentions is (1) contingent on the mode of education (active, e.g. business plan seminar, vs reflective, e.g. theory lectures), (2) contingent on the regional context and (3) complemented by individual-level influences such as role models or work experience. Results show that active modes of entrepreneurship education directly increase intentions and attitudes, whereas the impact of reflective modes depends on the regional context. Parental role models and work experience are found to complement entrepreneurship education in different ways. The findings have important implications for theory building as well as for the practice of teaching entrepreneurship.
Keywords: A20; I23; O31; R19; 330; Entrepreneurship education; knowledge spillover; entrepreneurial intentions; theory of planned behavior; Unternehmer; Betriebswirtschaftsstudium; Führungskräfteausbildung; Wissenstransfer; Selbstständige; Motivation; Region; Deutschland